Propylene / 1-pentene random copolymers : preparation, characterisation and commercialisation - Potgieter, A. H. (Antonie Hermanus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2002.